Una década de publicaciones sobre el anarquismo español: 2000-2011 - Joël Delhom (Cahiers de Civilisation Espagnole Contemporaine)
Books, booklets and dissertations in Spanish, Catalan, Galician and French published between 2000 and 2011, excluding new editions of books previously published between 1970 and 1999. This bibliography, organized in seven chapters combining chronological periods, sets of themes and geographic areas, comprises about 300 references. The presentation includes a brief commentary upon each chapter.